Development of Cotton and Wheat Variety Certification Using Isr-Pcr Markers - Rashidova Dilbar; Yakubov Muzaffar; Mammadov Normukhammad (BIO Web of Conferences, 2023)
It is shown in this article, that electrophoretic spectrum of gliadin proteins consists of specific components in each variety. Among analyzed varieties there were homogeneous varieties by electrophoretic gliadin spectra as well as heterogeneous varieties. The wheat varieties Krasnodar99, Kroshka, Zimnitsa and Tanya were homogeneous, while the varieties Vostorg, Grom, Zvezda, Andizhan-2, Asr, Durdona, Dustlik, Yaksart and Chillaki were heterogeneous with 2-3 phenotypes in their electrophoretic spectrum. In the varieties Zvezda and Sila, three phenotypes and in the variety Thunder two phenotypes were found. In each variety, in addition to the main spectrum, phenotypes up to 5% were found with an electrophoretic spectrum different from the main one. In the variety Andijan-2 four biotypes with percent ratio of 80:5:5:10 and this variety has the highest number of biotypes of heterogeneous varieties. In Asr variety 3 heterogeneous biotypes with 85:10:5 ratio, in Yenbosh variety 3 biotypes with 80:10:10 ratio, in Durdon variety 2 biotypes with 70:30 ratio and in Chillaki variety also 2 biotypes with 80:20 ratio were identified. Molecular marking and genotype passporting are used in basic genetics and in applied biological science. Some wheat varieties cultivated in Uzbekistan were found to be heterogeneous and have several phenotypes in their genotype according to the electrophoretic spectrum of gliadins. To accurately determine whether the identified phenotype belongs to a particular variety, it is necessary to screen all varieties from different seed growing farms, create a catalogue of EF-spectrum passports and evaluate the varietal purity of each variety.